A phase 1 trial of NY‐ESO‐1‐specific TCR‐engineered T‐cell therapy combined with a lymph node‐targeting nanoparticulate peptide vaccine for the treatment of advanced soft tissue sarcoma. Issue 12 (17th February 2023) - Ishihara, Mikiya; Nishida, Yoshihiro; Kitano, Shigehisa; Kawai, Akira; Muraoka, Daisuke; Momose, Fumiyasu; Harada, Naozumi; Miyahara, Yoshihiro; Seo, Naohiro; Hattori, Hiroyoshi; Takada, Kohichi; Emori, Makoto; et al.
Abstract: The efficacy of immune checkpoint inhibitors is limited in refractory solid tumors. T‐cell receptor gene‐modified T (TCR‐T)‐cell therapy has attracted attention as a new immunotherapy for refractory cold tumors. We first investigated the preclinical efficacy and mode of action of TCR‐T cells combined with the pullulan nanogel:long peptide antigen (LPA) vaccine in a mouse sarcoma model that is resistant to immune checkpoint inhibition. Without lymphodepletion, the pullulan nanogel:LPA vaccine markedly increased the number of TCR‐T cells in the draining lymph node and tumor tissue. This change was associated with enhanced CXCR3 expression in TCR‐T cells in the draining lymph node. In the phase 1 trial, autologous New York esophageal squamous cell carcinoma 1 (NY‐ESO‐1)‐specific TCR‐T cells were infused twice into HLA‐matched patients with NY‐ESO‐1 + soft tissue sarcoma (STS). The pullulan nanogel:LPA vaccine contains an epitope recognized by TCR‐T cells, and it was subcutaneously injected 1 day before and 7 days after the infusion of TCR‐T cells. Lymphodepletion was not performed. Three patients with refractory synovial sarcoma (SS) were treated. Two out of the three patients developed cytokine release syndrome (CRS) with low‐to‐moderate cytokine level elevation. We found obvious tumor shrinkage lasting for more than 2 years by tumor imaging and long‐term persistence of TCR‐T cells in one patient. In conclusion, NY‐ESO‐1‐specific TCR‐T‐cell therapy plus vaccination with the pullulan nanogel carrying an LPA containing the NY‐ESO‐1 epitope without lymphodepletion is feasible and can induce promising long‐lasting therapeutic effects in refractory SS (Registration ID: JMA‐IIA00346). Abstract : What's new? T‐cell receptor (TCR) gene‐modified T‐cell therapy is a promising therapeutic approach for advanced tumors. Achieving clinical efficacy, however, remains problematic, owing to limitations in delivery and targeting. The present study explored the impact of combining TCR T‐cells with a pullulan nanogel drug delivery system containing a long peptide antigen (LPA) vaccine. Preclinical investigations show that, in the absence of preconditioning by lymphodepletion, pullulan nanogel:LPA vaccine increased TCR‐T cell numbers in lymph node and tumor tissue. In human patients, without lymphodepletion, pullulan nanogel loaded with LPA containing the tumor antigen NY‐ESO‐1 showed potential in inducing lasting effects in refractory synovial sarcoma.